2002
DOI: 10.1080/10611860290007540
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluations of Dihydroquinoline- and Dihydroisoquinoline-based Targetor Moieties for Brain-specific Chemical Delivery Systems

Abstract: Brain-targeted delivery of various drugs can be successfully achieved by chemical delivery systems (CDS) that contain a 1,4-dihydropyridine-based redox targetor moiety and undergo a sequential metabolism. However, the susceptibility of this moiety toward hydration in acidic media may limit the shelf-life of such compounds in aqueous formulation. Here, a systematic investigation of the chemical stability toward oxidation and hydration of ester and amide derivatives of 3-substituted 1,4-dihydropyridine, 1,4-dihy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 0 publications
0
29
1
Order By: Relevance
“…Thus, [ 11 C]DHQ1 responded to the changes of redox status in mouse brain homogenate. A previous study has shown that unlabeled DHQ1 was stable in rat brain homogenate without any sign of oxidation within the time of experiment (6 hours), 9 whereas our study showed that [ 11 C]DHQ1 was rapidly oxidized in mouse brain homogenate (Figure 2). This may be due to species differences in the activity of enzymes involved in the oxidation of DHQ1 between mouse and rat.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…Thus, [ 11 C]DHQ1 responded to the changes of redox status in mouse brain homogenate. A previous study has shown that unlabeled DHQ1 was stable in rat brain homogenate without any sign of oxidation within the time of experiment (6 hours), 9 whereas our study showed that [ 11 C]DHQ1 was rapidly oxidized in mouse brain homogenate (Figure 2). This may be due to species differences in the activity of enzymes involved in the oxidation of DHQ1 between mouse and rat.…”
Section: Discussioncontrasting
confidence: 76%
“…This compound was synthesized by the hydrolysis of quinoline-3-carbonitrile in the same manner as described previously. 9 3-Carbamoyl-1-methylquinolinium iodide (Q1 + ). This compound was synthesized by the reaction of quinoline-3-carboxamide with CH 3 I in the same manner as described previously.…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…A similar prodrug approach has been advocated by Bodor et al (2002), for drug-targeting of blood-brain barrier. They showed that several hydrophilic compounds including opioid peptides were successfully delivered to the central nervous system by using specific prodrug approaches (Prokai et al, 1999;Bodor et al, 2002;Tapfer et al, 2004), one of which was to incorporate a lipophilic ester into the active form for the increase of permeability through blood-brain barrier and the retention of the generated active form within the target site.…”
Section: Discussionmentioning
confidence: 99%